2021
DOI: 10.3389/fimmu.2021.621311
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Origins of Extracellular DNA Traps

Abstract: Extracellular DNA traps (ETs) are evolutionarily conserved antimicrobial mechanisms present in protozoa, plants, and animals. In this review, we compare their similarities in species of different taxa, and put forward the hypothesis that ETs have multiple origins. Our results are consistent with a process of evolutionary convergence in multicellular organisms through the application of a congruency test. Furthermore, we discuss why multicellularity is related to the presence of a mechanism initiating the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 154 publications
(157 reference statements)
0
24
0
Order By: Relevance
“…The common purpose of ETosis in these species is overwhelmingly in defense against pathogenic infection, perhaps a strategy that emerged early on in eukaryotic evolution. Using a congruency test, Ramos-Martinez et al found that the ETs across these species exhibited convergent evolution, and the transition from being unicellular to multicellular organisms was crucial for their emergence [ 42 ].…”
Section: A Brief History Of the Discovery Of Netsmentioning
confidence: 99%
“…The common purpose of ETosis in these species is overwhelmingly in defense against pathogenic infection, perhaps a strategy that emerged early on in eukaryotic evolution. Using a congruency test, Ramos-Martinez et al found that the ETs across these species exhibited convergent evolution, and the transition from being unicellular to multicellular organisms was crucial for their emergence [ 42 ].…”
Section: A Brief History Of the Discovery Of Netsmentioning
confidence: 99%
“…The eosinophil extracellular traps process also depends on the production of ROS, such as neutrophil and mast cells extracellular traps. mtDNA release was also observed in B, T, and NK cells in response to oligodeoxynucleotides [ 105 ].…”
Section: Mechanisms Of Release Of Mtdna In Biological Fluidsmentioning
confidence: 99%
“…The common purpose of ETosis in these species is overwhelmingly in defence against pathogenic infection, perhaps a strategy that emerged early on in eukaryotic evolution. Using a congruency test, Ramos-Martinez et al found that the ETs across these species exhibited convergent evolution, and the transition from being unicellular to multicellular organisms was crucial for their emergence (42).…”
Section: A Brief History Of the Discovery Of Netsmentioning
confidence: 99%